A proposal of performance measurement and management model for 5S sustainability in manufacturing SMEs: A Review - Nashrullah SETIAWAN; Mohd Rizal SALLEH; Hambali A ARIFF; Muhamad Arfauz A RAHMAN; Effendi MOHAMAD; Mohd Amri SULAIMAN; Faizuddin Firdaus ZAINI; Teruaki ITO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2021)
The practice of 5S principles in manufacturing small and medium enterprises (SMEs) has been widely discussed in scientific studies related to the critical success factors (CSFs) and challenges for improving organizational performance. The importance of performance measurement for sustaining 5S becomes a strategic value in the improvement process and elimination of waste. In previous studies, the performance measurement of 5S practices is commonly viewed as an auditing process continuously. However, the studies of performance measurement and management (PMM) for the sustainability of 5S practices as a control system are still limited. Also, the performance measurement model needs to be designed for measuring the potential barriers of 5S sustainability. Therefore, this study has a motivation to develop a conceptual model in designing PMM for the sustainability of 5S practices that are carried out both empirically and philosophically to enhance quality and productivity. So, the objective of this paper is to conduct the literature reviews on how to propose a model of PMM for 5S sustainability in manufacturing SMEs based on CSFs and the integrated theoretical framework. The review methodology provides a systematic review step that encompasses collecting the database, qualitative analysis of the database, synthesizing the relevant theory, and proposing a conceptual model. This paper found the critical point for developing the PMM model of 5S sustainability including the step of sustainability building, dimensional control system, and sustainability indicators. For further research, it needs an analyzing study to assess the relationship among the factors that contribute to the performance assessment of 5S practices.